ABA learning via ASP - De,Angelis E; Proietti,M; Toni,F (Open Publishing Association, 2023)
Recently, ABA Learning has been proposed as a form of symbolic machine learning for drawing Assumption-Based Argumentation frameworks from background knowledge and positive and negative examples. We propose a novel method for implementing ABA Learning using Answer SetProgramming as a way to help guide Rote Learning and generalisation in ABA Learning.